Acute morphine alters GABAergic transmission in the central amygdala during naloxone-precipitated morphine withdrawal: role of cyclic AMP - Bajo, Michal; Madamba, Samuel G.; Roberto, Marisa; Siggins, George R. (Frontiers in Integrative Neuroscience, 2014)
The central amygdala (CeA) plays an important role in opioid addiction. Therefore, we examined the effects of naloxone-precipitated morphine withdrawal (WD) on GABAergic transmission in rat CeA neurons using whole-cell recordings with naloxone in the bath. The basal frequency of miniature inhibitory postsynaptic currents (mIPSCs) increased in CeA neurons from WD compared to placebo rats. Acute morphine (10 M) had mixed effects (> 20% change from baseline) on mIPSCs in placebo and WD rats. In most CeA neurons (64%) from placebo rats, morphine significantly decreased mIPSC frequency and amplitude. In 32% of placebo neurons, morphine significantly increased mIPSC amplitudes but had no effect on mIPSC frequency. In WD rats, acute morphine significantly increased mIPSC frequency but had no effect on mIPSC amplitude in 41% of CeA neurons. In 45% of cells, acute morphine significantly decreased mIPSC frequency and amplitude. Pre-treatment with the cyclic AMP inhibitor (R)-adenosine, cyclic 3’,5’-(hydrogenphosphorothioate) triethylammonium (RP), prevented acute morphine-induced potentiation of mIPSCs. Pre-treatment of slices with the Gi/o G-protein subunit inhibitor pertussis toxin (PTX) did not prevent the acute morphine-induced enhancement or inhibition of mIPSCs. PTX and RP decreased basal mIPSC frequencies and amplitudes only in WD rats. The results suggest that inhibition of GABAergic transmission in the CeA by acute morphine is mediated by PTX-insensitive mechanisms, although PTX-sensitive mechanisms cannot be ruled out for non-morphine responsive cells; by contrast, potentiation of GABAergic transmission is mediated by activated cAMP signaling that also mediates the increased basal GABAergic transmission in WD rats. Our data indicate that during the acute phase of WD, the CeA opioid and GABAergic systems undergo neuroadaptative changes conditioned by a previous chronic morphine exposure and dependence.